A novel approach to district heating and cooling network design based on life cycle cost optimization. (1st March 2020) - Best, Robert E.; Rezazadeh Kalehbasti, P.; Lepech, Michael D.
Abstract: Piping layout, material, and dimension choices are essential in determining the initial capital costs and full operating costs of a district heating and cooling (DHC) network. While common practice aims to minimize initial capital costs or, in some cases, operational costs, this paper introduces a novel method for designing DHC network layouts for minimum total life-cycle cost by introducing additional engineering design parameters related to pipe sizing, heat losses, and pumping energy. The proposed mixed-integer linear programming solution satisfies the thermal and hydraulic constraints on the network while minimizing the objective function of total cost over the lifetime of the network. The method is tested with three case studies. Results show improvement in reducing total life-cycle costs of the network compared to approaches that consider only capital or operating costs and exclude network dimensioning. Highlights: A novel optimization method for district heating and cooling pipe layout is presented. Unlike common practice, pipe sizing and annual energy cost drive network design. Pumping energy and heat loss are linearized to create mixed-integer linear problem. Method improves design approaches that consider only capital or operating cost. Method improves solutions from prior life-cycle cost optimization approaches.